Conformational dependence of electron transfer across de novo designed metalloproteins. - Mutz, M W (1996)
Flash photolysis and pulse radiolysis measurements demonstrate a conformational dependence of electron transfer rates across a 16-mer helical bundle (three-helix metalloprotein) modified with a capping CoIII(bipyridine)3 electron acceptor at the N terminus and a 1-ethyl-1'-ethyl-4,4'- bipyridinium donor at the C terminus. For the CoIII(peptide)3-1-ethyl-1'-ethyl-4,4'-bipyridinium maquettes, the observed transfer is a first order, intramolecular process, independent of peptide concentration or laser pulse energy. In the presence of 6 M urea, the random coil bundle (approximately 0% helicity) has an observed electron transfer rate constant of kobs = 900 +/- 100 s-1. In the presence of 25% trifluoroethanol (TFE), the helicity of the peptide is 80% and the kobs increases to 2000 +/- 200 s-1. Moreover, the increase in the rate constant in TFE is consistent with the observed decrease in donor-acceptor distance in this solvent. Such bifunctional systems provide a class of molecules for testing the effects of conformation on electron transfer in proteins and peptides.